Abstract 119: VP‐shunting for IIH complicated by CVST, Dural AV Fistula and Status Epilepticus ‐ Endovascular Perspective - Omar Choudhury (Stroke: Vascular and Interventional Neurology)
Introduction Cerebral venous sinus thrombosis (CVST) presents diagnostic challenges, especially in its overlap with idiopathic intracranial hypertension (IIH). Timely neuroimaging using MRI and MRV is crucial to avoid misdiagnosing CVST as IIH [1]. VP shunts, although beneficial in IIH, have significant failure rates and potential complications [2]. Few cases in the literature report occurrence of CVST or worsening of CVST after VP‐shunt placement [3]. The close relationship between CVST and dural AVF further complicates the clinical picture [4]. Endovascular intervention may present challenges with respect to chronic CVST, which can be mistaken for IIH. Methods We report a rare case of a 73‐year‐old woman with a past medical history of diabetes, hypertension, and hyperlipidemia who presented with confusion, disorientation, and lethargy. Comprehensive neurological evaluation, neuroimaging, lumbar puncture, EEG monitoring and treatment interventions, including VP shunt placement, cerebral angiogram, onyx embolization, and systemic anticoagulation, were performed. Results The patient initially presented with symptoms of progressive headaches, transient visual obscurations, and papilledema, suggestive of IIH. After lumbar puncture revealed elevated opening pressures, she underwent VP shunt placement. Her postoperative period was complicated by status epilepticus, extensive venous sinus thrombosis, and multiple dural AV fistulas. A cerebral angiogram showed a left occipital AV fistula, treated with onyx embolization. Repeat imaging indicated dural over‐shunting, yet this was negated upon Neurosurgical evaluation. A subsequent diagnostic cerebral angiogram was unable to clear the chronic CVST, but the patient responded positively to systemic anticoagulation and seizure management. Conclusion This case underscores the need for caution when considering VP shunting in patients with elevated intracranial pressure symptoms. Our findings emphasize the importance of an early MRV to rule out CVST and determine the appropriate treatment approach. Iatrogenic progression of CVST, VP shunt over‐drainage, and status epilepticus are serious complications that can arise from a misdiagnosis of IIH. Additionally, this case offers an endovascular perspective on patients who have chronic CVST, which can be misdiagnosed as IIH. Endovascular interventions including onyx AV fistula embolization and angiographic evaluation of the patient provided significant diagnostic and therapeutic benefits, and ultimately the patient was discharged with improved mentation.